Implementation of Education for Sustainable Development in Elementary School Science Learning: A Systematic Review - Irwandani; Afra Mahlia Putri; Chairul Amriyah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2026)
Rapid global change, including environmental degradation and climate change, demands the strategic role of education in fostering sustainability awareness from an early age. This study aims to systematically review and synthesize research findings related to the implementation of Education for Sustainable Development (ESD) in Natural Sciences (IPA) learning in elementary schools. This study uses a Systematic Literature Review (SLR) approach by following the PRISMA 2020 guidelines to identify, screen, and analyze relevant studies published in the range of 2021 to 2025. Articles are obtained from selected academic databases by applying the inclusion and exclusion criteria that have been set. A total of eleven articles met the eligibility criteria and were analyzed using qualitative thematic synthesis. The findings show that the implementation of ESD in elementary school science learning is generally carried out through active learning models, the development of ESD-based media and teaching materials. All of the studies analyzed reported the positive impact of ESD implementation on cognitive, social-emotional and 21st-century skills aspects. Practically, these findings recommend that primary school teachers integrate sustainability issues through active learning models, project-based activities, and the use of contextual media. In addition, the results of these findings can be a reference for curriculum developers and education policymakers in strengthening the integration of ESD principles in science learning in elementary schools.